Isolation, structure elucidation and bioactivity profiling of lyso-ornithine lipids from the marine bacterium Lacinutrix sp. - Jawad, Jawad (UiT Norges arktiske universitet, 2021)
From previous work, it was identified two analytes of interest, produced by Lacinutrix sp. The two analytes are iso-branched lyso-ornithine lipids with only one CH2 group differing between the two compounds, in the hydrocarbon chain (lysoC15:0 and C16:0). The bacterium was isolated from the marine sponge Halicondria sp. that was collected beside Bjørnøya, on a research cruise in 2009. The analytes were identified and nominated for isolation based on bioactivity of fractionated extract from the bacterium. Unfortunately, the isolated quantities of the two were too low to allow bioactivity profiling. In the current project, the aim was therefore to generate more of the pure compounds to further perform bioactivity profiling. This was done by performing a large-scale fermentation of the bacterium. Further, the exudates of the bacterium were extracted, fractionated, and the targeted compounds were purified then tested for bioactivity in a dose-response manner on a variety of assays, with the aim to generate bioactivity data. The isolation is therefore targeted, meaning that we already knew what compounds that are to be isolated. The bioactivity results showed an antimicrobial activity against S. agalactiae and a modest antimicrobial activity against E.faecialis and S. aureus, only for compound 1. No antimicrobial activity was displayed against the tested Gram-negative bacteria for both compounds. Cytotoxic assay was also run for the cell line A2058 (human melanoma), and activity was observed only for compound 2. No cytotoxic activity was observed against the cell line MRC-5 (non-malignant cells). These surprising results of almost identical structures indicate that the length of the hydrocarbon chain contribute to differences in activity, as the results display a selective activity against bacterial cells for compound 1 and a selective activity against human melanoma cells for compound 2. No cytotoxic activity was observed against the cell line MRC-5 (non-malignant cells)